Targeting eIF5A2 inhibits prostate carcinogenesis, migration, invasion and metastasis in vitro and in vivo. Issue 1 (1st January 2020) - Zhong, Xiulong; Xiu, Hong; Bi, Yanan; Zhang, Hongmei; Chang, Laizhen; Diao, Huifeng
ABSTRACT: Overexpression of eukaryotic initiation factor- 5A2 (eIF5A2) has been implicated in promoting tumor cell migration and invasion in many cancers. However, whether eIF5A2 could be as the target for prostate cancer (PCa) treatment is still unknown. In this study, small interfering RNA specific for eIF5A2 (eIF5A2 siRNA) and lentivector for eIF5A2 shRNA (Lv-eIF5A2 shRNA) was performed to down-regulate eIF5A2 expression in PCa PC-3 M IE8 cells and in animal tumor model, respectively. The biological function of eIF5A2 siRNA or Lv-eIF5A2 shRNA on PC-3 M IE8 cell growth, apoptosis, migration, invasion and lung metastasis were explored. The results showed that targeting eIF5A2 inhibited PC-3 M IE8 cell invasion, migration, proliferation and increased cell apoptosis in vitro, and inhibited tumor growth and lung metastasis in vivo . Analysis of eIF5A2 signaling pathways in the clonal derivatives showed a decrease in MMP-2 and MMP-9 activation and increase in bcl-2 expression. We therefore concluded that therapies targeting the eIF5A2 signaling pathway may be more effective to prevent organ metastasis and primary tumor formation.